Data aquisition for sensor systems - Taylor, H. Rosemary (Sensor physics and technology (Chapman & Hall), 1997)
The text is ideal for use by a wide range of readers; for scientists and engineers of any discipline who wish to use data acquisition in their work and need to make an informed selection from the many systems of hardware and software available; for circuit engineers designing electronic instruments which need to incorporate data acquisition; and for students of electrical and electronic engineering courses, all of whom will encounter the topics of measurement and instrumentation.